The Relationship Between Dowry And Education: The Practice Of Giving Dowry In Padang Sidempuan - Pasaribu, Ahmad Rusli; Siregar, Fatahuddin Aziz (Jurnal El-Thawalib, 2023)
The research problem is the influence of women's education on marriage dowries in the city of Padang Sidimpuan. Giving dowry is mandatory in marriage while education is experience in studying in formal educational institutions so giving dowry based on education is a practice in society in giving marriage dowries. Articles 30 and 33 state that the determination of the dowry must be made by both parties and must be made in cash, but in a state of debt at the time after the contract, it does not cancel the marriage. The research methodology used is qualitative field research, namely research conducted by collecting primary and secondary data on the phenomenon that is happening directly. this research which becomes the primary data is data obtained directly from the research subject. Primary data is the influence of education in determining the dowry and public opinion on the matter in Padang Sidimpuan. Primary legal materials are the Al-Qur’an and Hadist, Book translation dictionary. Furthermore, data collections techniques were carried out by interview, observation, and documentation. The result of this study are, firstly Education is indeed the determinant of dowry in marriages in the city of Padang Sidempuan, this is supported by several factors such as the request of the prospective wife, and secondly, the dowry given is a form of honoring the wife.